Mauriac Syndrome: A Comprehensive Review of a Rare Complication of Poorly Controlled Type 1 Diabetes Mellitus (Janaki Medical College Journal of Medical Science, 2025)
Mauriac syndrome (MS) is a rare complication of type 1 diabetes mellitus (T1DM) in children and adolescents. It is caused by consistently insufficient glycemic control and manifests as hepatomegaly with growth retardation. It is unclear what variables lead to delayed puberty and delayed growth in MS. Since the discovery of insulin analogues and long- and intermediate-acting insulin, the distinct clinical signs and symptoms of MS have rarely been reported. Lack of insulin as a growth factor, hypercortisolism, and insufficient glucose in tissues can all play a part in the multifactorial pathophysiology of development and pubertal delay. Mauriac syndrome can be characterized by short stature, moon facies, hepatomegaly, protuberant abdomen, pubertal delay, proximal muscle wasting, reduced joint mobility, and nephropathy/retinopathy. These changes are linked to the duration of poor glycemic control and microvascular consequences. To achieve optimal glycemic regulation, the clinician needs to have a high index of suspicion about Mauriac syndrome. This review aims to highlight a comprehensive review of a rare complication of poorly controlled type 1 Diabetes Mellitus.